2020
DOI: 10.1007/s13760-020-01513-0
|View full text |Cite
|
Sign up to set email alerts
|

An intronic variant in BRAT1 creates a cryptic splice site, causing epileptic encephalopathy without prominent rigidity

Abstract: BRAT1-related neurodevelopmental disorders are characterized by heterogeneous phenotypes with varying levels of clinical severity. Since the discovery of BRAT1 variants as the molecular etiology of lethal neonatal rigidity and multifocal seizure syndrome (RMFSL, OMIM 614498), these variants have also been identified in patients with milder clinical forms including neurodevelopmental disorder with cerebellar atrophy and with or without seizures (NEDCAS, OMIM 618056), epilepsy of infancy with migrating focal sei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…Since the BRAT1 was first reported as the causative gene of RMFSL (Puffenberger et al, 2012), 45 mutations in the BRAT1 have been reported to date according to the Human Gene Mutation Database HGMD (http://www.hgmd.org/; Professional 2022.1) and the existing literature, including 20 missense/nonsense mutations, 8 splice mutations, 9 small deletions, 5 small insertions/duplications, and 3 gross deletions mutations (Figure 5, Table 1) (Capalbo et al, 2019;Colak et al, 2020;Fernández-Jaén et al, 2016;Hanes et al, 2015;Heide et al, 2020;Li et al, 2021;Na et al, 2020;Qi et al, 2022;Scheffer et al, 2020;Szymańska et al, 2018;Wu et al, 2021). In this study, we found a sixth splice site mutation c.431-2A>G (Colak et al, 2020;Horn et al, 2016;Srivastava et al, 2014;Stödberg et al, 2020;Rudolf et al, 2020). To determine the effect of this splicing variant, Sanger sequencing analysis of the cDNA covering exons 2-8 of the BRAT1 showed that the 3′-splice site acceptor c.431-2A>G variant activated a cryptic acceptor splice site, which resulted in the loss of 29 nucleotides and generation of a premature stop codon at code 180, producing a truncated BRAT1 (c.432_460del; p.Ala145Argfs*36).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the BRAT1 was first reported as the causative gene of RMFSL (Puffenberger et al, 2012), 45 mutations in the BRAT1 have been reported to date according to the Human Gene Mutation Database HGMD (http://www.hgmd.org/; Professional 2022.1) and the existing literature, including 20 missense/nonsense mutations, 8 splice mutations, 9 small deletions, 5 small insertions/duplications, and 3 gross deletions mutations (Figure 5, Table 1) (Capalbo et al, 2019;Colak et al, 2020;Fernández-Jaén et al, 2016;Hanes et al, 2015;Heide et al, 2020;Li et al, 2021;Na et al, 2020;Qi et al, 2022;Scheffer et al, 2020;Szymańska et al, 2018;Wu et al, 2021). In this study, we found a sixth splice site mutation c.431-2A>G (Colak et al, 2020;Horn et al, 2016;Srivastava et al, 2014;Stödberg et al, 2020;Rudolf et al, 2020). To determine the effect of this splicing variant, Sanger sequencing analysis of the cDNA covering exons 2-8 of the BRAT1 showed that the 3′-splice site acceptor c.431-2A>G variant activated a cryptic acceptor splice site, which resulted in the loss of 29 nucleotides and generation of a premature stop codon at code 180, producing a truncated BRAT1 (c.432_460del; p.Ala145Argfs*36).…”
Section: Discussionmentioning
confidence: 99%
“…Since the BRAT1 was first reported as the causative gene of RMFSL (Puffenberger et al, 2012), 45 mutations in the BRAT1 have been reported to date according to the Human Gene Mutation Database HGMD (http://www.hgmd.org/; Professional 2022.1) and the existing literature, including 20 missense/nonsense mutations, 8 splice mutations, 9 small deletions, 5 small insertions/duplications, and 3 gross deletions mutations (Figure 5, Table 1) (Capalbo et al, 2019; Colak et al, 2020; Fernández‐Jaén et al, 2016; Hanes et al, 2015; Heide et al, 2020; Li et al, 2021; Na et al, 2020; Qi et al, 2022; Scheffer et al, 2020; Szymańska et al, 2018; Wu et al, 2021). In this study, we found a sixth splice site mutation c.431‐2A>G (Colak et al, 2020; Horn et al, 2016; Srivastava et al, 2014; Stödberg et al, 2020; Rudolf et al, 2020). To determine the effect of this splicing variant, Sanger sequencing analysis of the cDNA covering exons 2–8 of the BRAT1 showed that the 3′‐splice site acceptor c.431‐2A>G variant activated a cryptic acceptor splice site, which resulted in the loss of 29 nucleotides and generation of a premature stop codon at code 180, producing a truncated BRAT1 (c.432_460del; p.Ala145Argfs*36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it is involved in p53‐mediated apoptosis, cellular growth signaling, and mitochondrial homeostasis (Aglipay et al, 2006; So & Ouchi, 2014). Recessive BRAT1 mutations were originally reported to cause rigidity and multifocal seizure syndrome, lethal neonatal (RMFSL, MIM# 614498), a rare congenital disorder characterized by microcephaly, hypertonia, autonomic instability, and intractable seizure, leading to death in the first 2 years of life (Burgess et al, 2019; Colak et al, 2020; Pourahmadiyan et al, 2020; Scheffer et al, 2020; Valence et al, 2019; Van Ommeren et al, 2018). Brain imaging was highly variable, ranging from normal findings to global atrophy (Srivastava et al, 2016).…”
Section: Figurementioning
confidence: 99%
“… 12 months Van Ommeren, 2018 [27] 1 Homozygous c.1395G > C, p.(Thr465Thr) Day 1 Myoclonic RMFSL Thinning of corpus callosum Diffuse encephalopathy, with frequent ictal activity from multiple cortical areas. 2 months Mahjoub, 2019 [28] 1 Homozygous c.185 T > A, p.(Val62Glu) No seizures reported None NEDCAS Cerebellar atrophy NA Alive at 24 years 2 No seizures reported None NEDCAS Cerebellar atrophy NA Alive at 7 years Colak, 2020 [29] 2 Homozygous c.1395G > C, p.(Thr465Thr) No seizures reported None NEDCAS Cerebellar atrophy Generalized epileptiform activity, migrating focal epileptiform activity, background deceleration. Alive at 7 years Pourahmadiyan, 2020 [30] 1 Homozygous c.2041G > T, p.(E681*) NK Focal seizures RMFSL NA NA 6 days Scheffer, 2020 [10] 1 Compound heterozygous c.964C > T, p.(Gln322*); c.2284C > T, p.(Gln762*) Day 1 Focal motor migrating between hemispheres EIMFS Underopercularization of the Sylvian fissure Multifocal epileptiform discharges, discontinuous background Ictal: focal seizure migrating from left central region to right hemisphere.…”
Section: Introductionmentioning
confidence: 99%